SISTEM INFORMASI KONTROL KUALITAS AIR BUDIDAYA IKAN LELE DALAM EMBER OTOMATIS BERDASARKAN AMONIA DAN PH BERBASIS IOT MENGGUNAKAN METODE FUZZY MAMDANI - Imamuddin , Muhammad; Mashuri , Chamdan; Augusta Jannatul Firdaus , Reza (Inovate, 2023)
This research aims to develop an Automatic Water Quality Control Information System based on IoT for catfish farming in buckets, using the fuzzy Mamdani method to measure Ammonia and pH levels. The background of this study involves the Sido Mulyo Dukuhdimoro Community Group, which has experienced a decline in harvest yields due to water quality issues. The current handling of Ammonia is done manually and is ineffective, necessitating technology that can address this problem.One proposed solution is the use of an IoT system that utilizes Ammonia and pH sensors to monitor water conditions in real-time. The use of fuzzy Mamdani logic is also suggested to enhance the automatic control system for Ammonia and pH levels. Based on experiments and implementations by the researchers, it is concluded that the fuzzy Mamdani method successfully monitors and controls water quality in IoT-based catfish farming. In 9 instances of blackbox testing, 2 discrepancies were found in the information system's water quality degree due to sensor differences and reference data. However, the water quality control system based on Ammonia and pH performed well. Calibration tests for Ammonia and pH using the Mutual Acceptance of Data (MAD) formula resulted in a difference of 0.01428 for Ammonia sensors (6 tests with an Ammonia test kit) and 0.01666 for pH sensors (7 tests with a digital pH meter).The automatic control system successfully maintains Ammonia and pH levels within a safe range for catfish, which is 0-0.6 ppm for Ammonia and pH 6.5-8.5. (BBPBAT, 2005). Keywords: Ammonia, pH, Sido Mulyo Community Group, BUDIKDAMBER, Catfish, Fuzzy Mamdani Logic, Automatic Control System, IoT.